Prevención y tratamiento de la infección de vías urinarias en gestantes. Riobamba 2021 - 2022 - Escudero Chávez, Evelyn Viviana (2022)
ABSTRACT: Urinary tract infection is one of the most common pathologies in pregnant women; therefore, this research addresses theoretical bases, including physiological and anatomical changes, epidemiology, most common etiology, diagnosis, treatment, prevention, and complications. This research project aims to determine the prevention and treatment measures used in pregnant women with urinary tract infections treated at the N°3 health center in Riobamba from January to December 2021. The population was 411 pregnant patients who attended the N°3 health center in Riobamba, of which 242 cases were reported as urinary tract infections in pregnancy. The research was a non-experimental retrospective observational study in which the database of the N°3 health center was analyzed, from which the necessary information was obtained on pregnant women who presented urinary tract infection during the determined period. As a result, of the 411 pregnant women who attended the health center and after prenatal control, where information on infection prevention was provided, 58.8% presented urinary tract infections. Of these 242 cases statistically analyzed under Microsoft Excel 2019 program, it is evident that there is a higher frequency of diagnosis of genital infection in pregnancy with 39.4%. In the second place, 17.8% is cataloged as infection of the urinary bladder in pregnancy, and 13.2% of the patients present infection of other parts of the urinary tract in pregnancy. Concerning the weeks of gestation and the prevalence of UTI, the study demonstrated a higher prevalence in the 27th week of gestation, with 24% of patients attending. Thus, the treatments used were also analyzed, the same ones reporting that the use of nitrofurantoin 100 mg every 12 hours represents 46.3% of frequency. In the second place, using cephalexin 500 mg every 8 hours is evidenced with 32.2% frequency, and finally, Fosfomycin 3g in a single dose with a frequency of 21.5%. It is concluded that the treatment and prevention measures used at the first level of care are based on the clinical practice guide issued by the Ministry of Health. In addition, there is a high prevalence of urinary tract infections in pregnant women, so the correct diagnosis and effective treatment can prevent complications that reduce maternal-fetal morbi-mortality.